Pengaruh Budaya Organisasi terhadap Semangat Kerja Karyawan melalui Kepuasan Kerja sebagai Variabel Mediasi pada PT. Surya Kembar di Gianyar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to determine the influence of organizational culture on job satisfaction, to determine the influence of organizational culture and job satisfaction partially on semangat kerjae and to find out the indirect influence of organizational culture on semangat kerjae through job satisfaction. The location of this study is in PT. Twin Solar in Gianyar. The sample in the study was 40 respondents. The research method used is quantitative. The data analysis techniques used in this study are Validity Test, Reability Test, and Sobel Test. Based on the results of the study, it can be seen that organizational culture has a positive and significant effect on semangat kerjae, organizational culture has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on semangat kerjae and organizational culture indirectly affects semangat kerjae through job satisfaction. The advice that researchers can give is PT. Surya Kembar in Gianyar is expected to make compensation policies that are in accordance with the duties or positions of employees, increase the amount of salary given and provide incentives to employees who are able to achieve targets.